Women’s Leadership From The Perspective Of Hadith - Fauziah, Nur (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This paper aims to examine women’s leadership from the perspective of the hadith. The approach used in this paper is qualitative, employing descriptive analytical methods and library research. This article attempts to present a textual and contextual analysis of women’s leadership in the public sphere. Based on the hadith interpretation conducted, the quality of the hadith narrated by al-Bukhari, al-Turmuzi, and al-Nasa’i regarding women’s leadership is generally sahih li dzatihi. Its chain of transmission meets the criteria for authenticity, and its textual source also meets the criteria for authenticity, namely, that tis free from syudzudz and ‘illah. The method of understanding the hadith on women’s leadership, when viewed textually, indicates a prohibition on women becoming leaders. However, when understood contextually, Islam does not prohibit women from becoming leaders in public affairs, even as heads of state, provided they are capable of carrying out the mandate. Given current developments, the hadith on female leadership must be understood contextually, as the circumstances at that time were very different from those of today. Women already possessed the authority and ability to lead, so there was No. harm in choosing and appointing women as leaders.